The Petrogenesis of Plagioclase-ultraphyric Basalts from La Réunion Island. (2nd July 2017) - Valer, Marina; Bachèlery, Patrick; Schiano, Pierre
Abstract: Plagioclase-bearing ultraphyric basalts, which can have up to 35% accumulative, millimetre-sized plagioclase crystals, were episodically erupted during some stages of building of La Réunion Island volcanoes. Selected rock samples were analysed from the two volcanoes of the island (four samples from Piton des Neiges and two from Piton de la Fournaise). We summarize the results of petrographic and geochemical studies of the whole-rocks and silicate melt inclusions trapped within plagioclase (An84·2–71·7 ) macrocrysts, which contain aliquots of the parental melts of their hosts. Melt inclusion compositions are used to discuss the origin of La Réunion plagioclase-bearing ultraphyric basalts, with special emphasis on the magma storage system that led to their production. Experimentally re-homogenized melt inclusions were analysed by electron microprobe and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) for their major and trace elements. Together with the textural observations, these results indicate that the host crystals are inherited, although their parental magma compositions are close to that of the host lava. Petrographic lines of evidence suggest that the plagioclase macrocrysts originate from batches of plagioclase-rich mush or fragments of anorthositic gabbro ripped from the magma chamber walls. The parental melts of the plagioclases evolve predominantly by clinopyroxene + plagioclase crystallization. The density contrasts between minerals and liquid allow their efficient segregation. We propose that plagioclases are collected below the magma chamber roof as a flotation cumulate, thereby forming plagioclase-rich mush and anorthositic gabbro, whereas clinopyroxenes sink. The plagioclase-ultraphyric basalts are derived from the remobilization of this mush, or fragments of the anorthositic cumulate, upon the input of a new batch of magma that triggers their eruption. We postulate that the periodic occurrence of these striking basalts during specific periods of the volcano's growth corresponds to decreases in the magma supply, which promoted plagioclase crystallization and its segregation by flotation. Finally, we suggest that the plagioclase-ultraphyric basalts from the Rivière des Remparts and Rivière de l'Est valleys, previously regarded as components of the Piton de la Fournaise volcano, are instead products of the declining activity of an older volcano, possibly Les Alizés volcano.